Aggressive combination therapy with intra-articular glucocorticoid injections and conventional disease-modifying anti-rheumatic drugs in early rheumatoid arthritis: second-year clinical and radiographic results from the CIMESTRA study. Issue 6 (18th September 2007) - Hetland, M L; Stengaard-Pedersen, K; Junker, P; Lottenburger, T; Hansen, I; Andersen, L S; Tarp, U; Svendsen, A; Pedersen, J K; Skjødt, H; Lauridsen, U B; Ellingsen, T; et al.
Abstract : Objective: To investigate whether clinical and radiographic disease control can be achieved and maintained in patients with early, active rheumatoid arthritis (RA) during the second year of aggressive treatment with conventional disease-modifying antirheumatic drugs (DMARDs) and intra-articular corticosteroid. This paper presents the results of the second year of the randomised, controlled double-blind CIMESTRA (Ciclosporine, Methotrexate, Steroid in RA) study. Methods: 160 patients with early RA (duration <6 months) were randomised to receive intra-articular betamethasone in any swollen joint in combination with step-up treatment with either methotrexate and placebo-ciclosporine (monotherapy) or methotrexate plus ciclosporine (combination therapy) during the first 76 weeks. At week 68 hydroxychlorochine 200 mg daily was added. From week 76–104 ciclosporine/placebo-ciclosporine was tapered to zero. Results: American College of Rheumatology 20% improvement (ACR20), ACR50 and ACR70 levels were achieved in 88%, 79% and 59% of patients in the combination vs 72%, 62% and 54% in the monotherapy group (p =  0.03, 0.02 and 0.6 between groups). The patients globally declined from 50 to 12 vs 52 to 9, with 51% and 50% in Disease Activity Score (DAS) remission, respectively. Mean (SD) progressions in total Sharp–van der Heijde scores were 1.42 (3.52) and 2.03 (5.86) in combination and monotherapy groups, respectively (not significant). Serum creatinine levels increased by 7% in the combination group (4% in monotherapy), but hypertension was not more prevalent. Conclusion: Continuous methotrexate and intra-articular corticosteroid treatment resulted in excellent clinical response and disease control at 2 years, and the radiographic erosive progression was minimal. Addition of ciclosporine during the first 76 weeks resulted in significantly better ACR20 and ACR50 responses, but did not have any additional effect on remission rate and radiographic outcome.